The Utilization of Digital Technology on Students' Learning Outcomes - Ranti, Lidiya Rima; Widya, Anggi; Sari, Mulia; Panamuan, Fortunata Blandina; Wiyono, Hadi (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
The rapid development of digital technology has brought significant changes to education in the 21st century. This study aims to analyze the utilization of digital technology in the learning process and its impact on students’ learning outcomes. The method used is qualitative with a literature review approach that identifies, evaluates, and synthesizes various previous studies published between 2020 and 2025. Data were obtained from national and international journals indexed in SINTA, DOAJ, and Google Scholar. The results of the review indicate that the integration of digital technology through the use of Learning Management Systems (LMS), multimedia applications, and interactive media has a positive effect on students’ motivation, engagement, and academic achievement. Teachers’ digital competence, institutional support, and the availability of infrastructure are key factors determining the success of digital technology implementation. However, there are still several challenges, such as limited access, digital literacy gaps between teachers and students, and uneven educational policies. In the long term, the use of digital technology contributes to the development of learning independence, critical thinking skills, and collaborative abilities that are essential for lifelong learning. Therefore, the utilization of digital technology needs to be accompanied by strengthened digital literacy, adequate infrastructure support, and continuous pedagogical innovation.